APPLICATION OF STATISTICAL DESIGN FOR THE ECONOMICAL PRODUCTION OF PHYTASE BY ASPERGILLUS NIGER USING SOLID STATE FERMENTATION - S. Mahmood; M. G. Shahid; M. Nadeem; R. Nelofer; M. Irfan (Journal of Animal and Plant Sciences, 2022)
The present study was aimed at high level and cost-effective production of phytase by Aspergillus niger under solid state fermentation adopting the response surface optimization method. Plackett-Burman design (PBD) and Central composite design (CCD) of Response surface methodology (RSM) were employed for screening and optimization of cultural conditions for maximum phytase production. Among 8 factors, incubation temperature, initial pH, incubation period, NH4NO3 and tween-40 were identified as significant factors by Plackett-Burman design (PBD) due to their positive effect on phytase production. Then, the optimization of these significant factors was conducted by Central Composite design (CCD), and incubation period (6 days), incubation temperature (35°C), initial pH (6), NH4NO3 (0.75%) and tween-40 (0.6%) were found to be optimum levels for best enzyme production. After statistical optimization, maximum amount of phytase production was obtained i.e. 406.45 IU/g, as it was 297.25 IU/g using conventional one factor at a time (OFAT) optimization approach. There was 1.37-fold increase in phytase yield using response surface methodology (RSM). These results indicated the efficacy of the response surface methodology to enhance phytase production by Aspergillus niger using solid state fermentation process.
Keywords: Aspergillus niger; Phytase enzyme; Response surface methodology (RSM); Solid state fermentation (SSF) and Agro-industrial waste